2018
DOI: 10.3389/fncel.2018.00280
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Protect Neurons in the Hippocampal CA3 Against Ischemia by Suppressing the Intracellular Ca2+ Overload

Abstract: In the hippocampus, delayed neuronal death is normally seen in neurons of the CA1 region but not in those of the CA3 region. Astrocytes have been reported to play multiple supporting or pathological roles in neuronal functioning. While evidence indicates that astrocytes could exert neuroprotective effects following ischemia, the possible underlying mechanisms remain unclear. We aimed to investigate the roles of astrocytes in the process of delayed neuronal death following transient forebrain ischemia. L-α-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Thus, although we cannot exclude the possibility that there might be a contribution of altered synaptic or microglia function without alteration of synaptic or microglia morphology, the observed loss of different astrocytic markers is compatible with a selective effect of l ‐AA on hippocampal astrocytes. A similar conclusion was reached in previous studies describing that after 72 h of l ‐AA injection in CA3 hippocampus of rats there is a selective damage of astrocytes, decreasing the number of these cells for at least 10 days 64 . Likewise, l ‐AA injected in the prefrontal cortex of rats also decreases astrocytic markers after 48 h, and this ablation of astroglial cells persists for at least 4 days and causes cognitive deficits 31 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, although we cannot exclude the possibility that there might be a contribution of altered synaptic or microglia function without alteration of synaptic or microglia morphology, the observed loss of different astrocytic markers is compatible with a selective effect of l ‐AA on hippocampal astrocytes. A similar conclusion was reached in previous studies describing that after 72 h of l ‐AA injection in CA3 hippocampus of rats there is a selective damage of astrocytes, decreasing the number of these cells for at least 10 days 64 . Likewise, l ‐AA injected in the prefrontal cortex of rats also decreases astrocytic markers after 48 h, and this ablation of astroglial cells persists for at least 4 days and causes cognitive deficits 31 .…”
Section: Discussionsupporting
confidence: 87%
“…A similar conclusion was reached in previous studies describing that after 72 h of l-AA injection in CA3 hippocampus of rats there is a selective damage of astrocytes, decreasing the number of these cells for at least 10 days. 64 Likewise, l-AA injected in the prefrontal cortex of rats also decreases astrocytic markers after 48 h, and this ablation of astroglial cells persists for at least 4 days and causes cognitive deficits. 31 Furthermore, mice injected with l-AA in the DG, exhibited a reduction of hippocampal GFAP immunoreactivity within 48 h and this astrocyte ablation was accompanied by the inhibition of contextual fear memory expression, suggesting that astrocytes are critically required for the formation of long-term memory.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, chronic unpredictable stress and starvation induced a reduction in astrocytes in the cerebral cortex 31 , 47 . A recent study showed that depletion of astrocytes by treatment with the gliotoxin L-α-aminoadipic acid (L-α-AAA) did not induce neuronal death in the hippocampal CA3 area without insults such as ischemia, but that the loss of astrocyte produced persistent Ca 2+ increase in the CA3 neurons after ischemia and reperfusion 48 . Thus, the reduction of astrocytes in the Xpnpep1 −/− hippocampus likely results in insufficient neuroprotection against intracellular Ca 2+ load during burst firing or the hyperactivation of neurons rather than direct induction of neurodegeneration in the Xpnpep1 −/− CA3 subfield.…”
Section: Discussionmentioning
confidence: 99%
“…В последнее время в связи с ростом интереса к глионейрональным взаимодействиям в норме и при патологии увеличилось число работ с применением L-AA как глиального токсина: для оценки роли астроцитов в эпилептогенезе, развитии депрессии [11][12][13], исследования нейропротекторных и провоспалительных функций астроглии, при моделировании паркинсонизма и ишемического повреждения мозга [14,15] и выяснения роли астроглии при когнитивных нарушениях [16,17]. Было показано повреждение астроцитов при введении L-AA в разные структуры мозга -гиппокамп [9], префронтальную кору [6] и стриатум [7], однако изменения других клеточных популяций описаны неполно и требуют отдельной оценки.…”
Section: Introductionunclassified